Deep space infections of neck - Kaluskar, S. (Springer-Verlag, 2007)
A retrospective study was performed on fourteen cases of deep cervical space infections in the neck admitted for diagnosis and treatment to the ENT Department, during a period of seven years from 1989–1997. Of the fourteen, four patients had Ludwig’s angina and of the fourteen, one had a very serious complication resulting in death. Early diagnosis and adequate treatment were of paramount importance. The role of tracheostomy and management of airway in deep cervical space infections of the neck is discussed to gether with bacteriology, antibiotic treatment and surgical management.